2016
DOI: 10.1007/s11239-016-1443-3
|View full text |Cite
|
Sign up to set email alerts
|

Classification of high-risk with cardiac troponin and shock index in normotensive patients with pulmonary embolism

Abstract: Accurate risk stratification of normotensive patients with acute pulmonary embolism (PE) require further investigation. We aimed to develop a simple model using clinical (shock index) and laboratory findings (cardiac Troponin, echocardiography) to assess the risk of 30-day mortality in normotensive patients with acute PE. In this retrospective study, 489 normotensive patients with acute PE diagnosed objectively. The primary end-point was defined as a all cause 30-day mortality. Shock index was calculated on ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…For each patient the following parameters were calculated: the sPESI score (score components are age >80 years, cancer, chronic cardiopulmonary disease, pulse ⩾110 beats per minute, systolic blood pressure <100 mm Hg and arterial oxygen saturation <90%, 4 the shock index (SI) (heart rate to systolic blood pressure ratio) 12 and the novel RI (oxygen saturation in air to respiratory rate ratio). All patients received anticoagulant treatment according to international guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…For each patient the following parameters were calculated: the sPESI score (score components are age >80 years, cancer, chronic cardiopulmonary disease, pulse ⩾110 beats per minute, systolic blood pressure <100 mm Hg and arterial oxygen saturation <90%, 4 the shock index (SI) (heart rate to systolic blood pressure ratio) 12 and the novel RI (oxygen saturation in air to respiratory rate ratio). All patients received anticoagulant treatment according to international guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, these investigators postulated that a shock index <1 alone is not a reliable indicator for the treatment of patients in outpatient settings. These authors 24 concluded that an external validation of the present study results in a multicenter cohort is advised to confirm the usefulness of the risk model before using it in clinical practice. In our study, the comparison between SI the day of ICU admission and the day of PE development showed a significant increase of SI the day of PE development (0.85 ± 0.26 vs. 0.95 ± 0.26; P = .027).…”
Section: F I G U R E 3 Comparison Between Shock Index (Si) the Day Ofmentioning
confidence: 83%
“…The shock index (SI), defined as heart rate (HR) divided by systolic blood pressure (SBP), should be more than 0.8‐1.0 in patients with shock, with higher values indicating more severe shock than lower values . A shock index (SI) of 1 or more is associated with high mortality . Currently, the shock index is not included in the standard risk assessment of PE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations